2016
DOI: 10.1371/journal.pntd.0005248
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide and Repellent Mixture Pour-On Protects Cattle against Animal Trypanosomosis

Abstract: BackgroundAfrican animal trypanosomosis (AAT), transmitted by tsetse flies and tick-borne diseases are the main constraints to livestock production in sub-Saharan Africa. Vector control methods such as pour-on offer individual protection against ticks but not against tsetse so far, for which protection has always been communal, through a reduction of their density. The latter requires the treatment of a large part of the herd in a given landscape and is not instantaneous.Methodology/Principal FindingsTwo prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although from our study, there was no signi cant difference between bovine trypanosomosis prevalence and body condition (Table 3), animals in good body condition score are more resilient to trypanosomosis infection compared to those in poor body condition in wet season as reported in Cameroon by (Gimonneau et al, 2016). The most likely possible explanation for lack of signi cant difference was that at the time of conducting this study, animals nutritional body reserves were not yet depleted and therefore no considerable variation in the body condition score was evident.…”
Section: Discussionmentioning
confidence: 46%
“…Although from our study, there was no signi cant difference between bovine trypanosomosis prevalence and body condition (Table 3), animals in good body condition score are more resilient to trypanosomosis infection compared to those in poor body condition in wet season as reported in Cameroon by (Gimonneau et al, 2016). The most likely possible explanation for lack of signi cant difference was that at the time of conducting this study, animals nutritional body reserves were not yet depleted and therefore no considerable variation in the body condition score was evident.…”
Section: Discussionmentioning
confidence: 46%
“…At the beginning of the survey, sampled cattle were treated with diminazene aceturate (DA), and dewormed with albendazole (Vermitan®, CEVA, Libourne, France) (7.5 mg/kg). They received every two months a pour-on formulation mixing cypermethrin and amitraz (Cypertraz®, CEVA, Libourne, France) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Today, although no insecticide resistance has been identified in tsetse, combination of different insecticides and molecules can significantly increase the formulation effect (Gimonneau et al 2016). Application of repellents on cattle to reduce trypanosomosis incidence was tested, and it was concluded that the repellent technology was not sufficiently efficient under natural tsetse challenge to merit commercial development (Bett et al 2010).…”
Section: Combination Of Repellent and Insecticidesmentioning
confidence: 99%
“…A new pour-on containing two insecticides, a pyrethroid synergist and a repellent have recently been developed and compared to a standard pour-on (i.e. based on one pyrethroid) (Gimonneau et al 2016). Results showed in the laboratory that the repellent and insecticides formulation was significantly more efficient than the classical formulation with a longer knockdown effect (37 and 28 days, respectively; Figure 5A).…”
Section: Combination Of Repellent and Insecticidesmentioning
confidence: 99%